2016
DOI: 10.1177/1535370216648022
|View full text |Cite
|
Sign up to set email alerts
|

Naturally derived biomaterials for addressing inflammation in tissue regeneration

Abstract: Tissue regeneration strategies have traditionally relied on designing biomaterials that closely mimic features of the native extracellular matrix (ECM) as a means to potentially promote site-specific cellular behaviors. However, inflammation, while a necessary component of wound healing, can alter processes associated with successful tissue regeneration following an initial injury. These processes can be further magnified by the implantation of a biomaterial within the wound site. In addition to designing biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 109 publications
(247 reference statements)
0
41
0
Order By: Relevance
“…In this chamber scCO 2 and the water additive were stirred vigorously until reaching thermodynamic equilibrium (about 15 min). At this point, flow was introduced into the 10 mL treatment chamber (6), which contained the matrix material. Constant flow was maintained by the syringe pump at 1 mL/min for the desired treatment time (usually about 1 h).…”
Section: Apparatus Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this chamber scCO 2 and the water additive were stirred vigorously until reaching thermodynamic equilibrium (about 15 min). At this point, flow was introduced into the 10 mL treatment chamber (6), which contained the matrix material. Constant flow was maintained by the syringe pump at 1 mL/min for the desired treatment time (usually about 1 h).…”
Section: Apparatus Development and Validationmentioning
confidence: 99%
“…This is a particular strength of naturally-derived biomaterials, which have recently been shown to promote constructive remodeling during tissue growth [4,5]. Decellularized ECM has also been shown to elicit an anti-inflammatory immune response, which may be related to a reduced risk of rejection [6,7]. Decellularization is accomplished using a variety of techniques, including physical [8], chemical [9], and enzymatic treatment methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…Following the proliferation phase, the tissue remodeling phase starts a few months after the injury. 21 This study showed that about 2 months after the implantation, the lumen became stable. This point might be considered as the transitional point from the proliferation phase to the remodeling phase.…”
Section: Discussionmentioning
confidence: 83%
“…Some inflammatory cytokines, including IL-1, IL-4, IL-6, IL-8, IL-18, and TGF-β1, are involved in the development of ischemic heart disease, myocardial infarction, and heart failure, thus, serving as potential targets for the development of some anti-ischemic therapies [24]. It was reported that the decellularized matrix has immunomodulatory properties and the ability to influence the host response in vivo [25]. us, we performed a protein chip assay to detect the expression of proinflammatory cytokines and anti-inflammatory cytokines when a cell or cell-scaffold construct was exposed to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%